2016
DOI: 10.1016/j.jmii.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors for HIV-1 transmitted drug resistance in voluntary clients for counseling and testing in Southern Taiwan

Abstract: In Southern Taiwan, the HIV TDR rate was 10.6% among those receiving VCT. Our findings suggest that sexual behavior may play an important role in HIV drug-resistant strain transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The mutations, M184V and K103N are commonly detected as multi-drug resistance mutations leading to the virological failure of a first-line NRTIs-and NNRTI-based regimens [16,28]. The appearance pattern of these drug resistance mutations was similar with those in previous studies in Indonesia, Malaysia, Taiwan, Turkey, and USA [17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. M184V is a common mutation in treated populations; however, it is very rare among…”
Section: Discussionsupporting
confidence: 69%
“…The mutations, M184V and K103N are commonly detected as multi-drug resistance mutations leading to the virological failure of a first-line NRTIs-and NNRTI-based regimens [16,28]. The appearance pattern of these drug resistance mutations was similar with those in previous studies in Indonesia, Malaysia, Taiwan, Turkey, and USA [17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. M184V is a common mutation in treated populations; however, it is very rare among…”
Section: Discussionsupporting
confidence: 69%
“…However, routine drug resistance testing has not been available to clinicians. According to a previous epidemiological study, the TDR rate is 8.0–11.1% in Taiwan [1214]. HIV-infected Taiwanese patients receive free HIV care based on the national treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance of TDR in Taiwan has revealed the impact of improved antiretroviral therapy (ART) regimens, although routine pre-treatment genotypic drug resistance testing (GRT) in ART-naïve patients is not conducted in Taiwan due to financial constraints. Previous studies have reported prevalence rates of TDR for protease (PR)/reverse transcriptase (RT) ( pol gene) of 8–11.1% [ 2 , 3 ] in northern Taiwan and 10.6% in southern Taiwan [ 4 ].…”
Section: Introductionmentioning
confidence: 99%